IMPLEMENTASI UNIVERSAL DESIGN FOR LEARNING (UDL) 2.0 DALAM PEMBELAJARAN DI PENDIDIKAN GURU SEKOLAH DASAR - Chelsi Yuliana S; Hidayah; Ria Ristiani; Edward (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aims to analyze the implementation of Universal Design for Learning (UDL) 2.0 in the learning process at the Elementary School Teacher Education Study Program (PGSD) of Cenderawasih University (UNCEN). The problem that underlies this research is the diversity of backgrounds of PGSD students, most of whom are not mature in learning activities in their home areas. This study uses a qualitative approach with semi-structured interview methods with six lecturers , a focus group discussion (FGD) with 50 students , and document analysis.The results show that lecturers have a good understanding of UDL 2.0 and implement it in the planning and execution of lectures. The implementation of UDL is seen in the provision of teaching materials in various formats (text, video, discussion) , the provision of diverse assignment options (essays, presentations, projects) , and the use of interactive learning methods to increase student motivation. The impact of this implementation is an increase in student engagement and understanding, as well as the creation of a more inclusive learning environment. However, the implementation of UDL still faces challenges such as time constraints, limited resources, and uneven training. The university, through the head of the study program, has initiated UDL training, but it has not been fully realized.